2021
DOI: 10.1155/2021/5525173
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Extraction Methods on Furanosesquiterpenoids Content and Antibacterial Activity of Commiphora myrrha Resin

Abstract: The oleo-gum-resin of Commiphora myrrha is one of the most known natural antimicrobial agents, mainly due to its furanosesquiterpenes. A validated method based on sample extraction by matrix solid-phase dispersion (MSPD) followed by high-performance column chromatography (HPLC) determination is applied to analyze two furanosesquiterpenoids, namely, 2-methoxyfuranodiene (CM-1) and 2-acetoxyfuranodiene (CM-2), existing in C. myrrha. The trial parameters that controlled the extraction prospective were studied and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
3
7
0
Order By: Relevance
“…Furthermore, Jagtap and Patil [55] and Abou Khalil et al [56] reported that MDA value was increased in the plasma as well as the pancreatic tissue of diabetes-induced rats, while it was significantly decreased by the treatment of diabetic animals with plant extracts (family Apiaceae). These results could be explained as mentioned by Alqahtani et al [10], who reported that C. myrrha has a great variation in furano-sesquiterpenoids, 2-methoxyfuranodiene and 2-acetoxyfuranodiene contents, possessing maximum antioxidant activity.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, Jagtap and Patil [55] and Abou Khalil et al [56] reported that MDA value was increased in the plasma as well as the pancreatic tissue of diabetes-induced rats, while it was significantly decreased by the treatment of diabetic animals with plant extracts (family Apiaceae). These results could be explained as mentioned by Alqahtani et al [10], who reported that C. myrrha has a great variation in furano-sesquiterpenoids, 2-methoxyfuranodiene and 2-acetoxyfuranodiene contents, possessing maximum antioxidant activity.…”
Section: Discussionsupporting
confidence: 62%
“…However, the molecular docking analysis score showed good binding efficiency for palmitic acid and pyrogallol than the isopropyl-isothiocyanate docking score. Similar findings by Alqahtani et al (2021) studied the effect of extraction methods on furanose sesquiterpenoids content and the antibacterial activity of Commiphora myrrha resin. Also, Rubab et al (2018) observed similar findings when studying Chinese cabbage extract's preservative effect on their molecular docking, antimicrobial, and antioxidant properties.…”
Section: Discussionsupporting
confidence: 59%
“…Molecular docking analysis validated the data obtained and offered intelligible evidence of observed antibacterial activity for compounds identified by GC–MS in RN and CS extracts. During replication, bacterial DNA gyrase has been shown to bind DNA and introduce negative supercoils at the expense of ATP hydrolysis ( Alqahtani et al, 2021 ). Moreover, dihydrofolate reductase (DHFR) converts dihydrofolate to tetrahydrofolate.…”
Section: Discussionmentioning
confidence: 99%
“…The contents of curzerene, methoxyfuranodiene, β-elemene, and α-pinene in the C. myrrh resin extract were quantitatively measured by GC-MS. The crude C. myrrh resin was extracted according to our previously described method [2,4]. Briefly, the dried oleogum resin of C. myrrh (1 kg) was extracted with 2 L of ethanol (95%) for 3 days using cold maceration.…”
Section: Assay Of the Four Volatile Compounds In Myrrh Extractmentioning
confidence: 99%
“…Commiphora myrrha (Nees) Engl. is a medicinal plant belonging to the genus Commiphora (Burseraceae family) and mainly grows in Yemen and the southern regions of Saudi Arabia [1,2]. C. myrrh is known to produce a natural compound (oleo-gum-resin), known as myrrh [3,4].…”
Section: Introductionmentioning
confidence: 99%